Electrocardiographic features in people involved in sports. Report І (a literature review) - Ye. L. Mykhaliuk; V. V. Syvolap (Zaporožskij Medicinskij Žurnal)
The article presents a modern vision of the electrocardiographic features in people involved in sports. The feasibility of ECG study in athletes is discussed. Recommendations for expanding the range of ECG changes related to athletes’ features are provided. Frequently encountered ECG changes in athletes, namely sinus bradycardia and first-degree atrioventricular block, are successively considered. The review presents our own results of ECG studies in athletes in certain sports of different gender and sports qualification.